2005
DOI: 10.1097/00019514-200504000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Capturing More Emergency Department Errors Via an Anonymous Web-based Reporting System

Abstract: A Web-based error reporting implemented in this manner may improve error reporting because of the convenience it offers and the option of anonymity. More reporting should create more opportunities for system improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Anonymous, Web-based reporting systems offer convenience and anonymity and are thought to improve error reporting. 17 Previously described error reduction techniques have included standardization of processes (adapting "critical pathways" and guidelines), formal teamwork training, 18 minimizing interruptions, 19 increasing attention to the highrisk elements of health care (such as patient care transitions), introducing redundancy and resilience into systems, 20 and implementation of appropriate information technology (such as prescription order entry systems).…”
Section: Discussionmentioning
confidence: 99%
“…Anonymous, Web-based reporting systems offer convenience and anonymity and are thought to improve error reporting. 17 Previously described error reduction techniques have included standardization of processes (adapting "critical pathways" and guidelines), formal teamwork training, 18 minimizing interruptions, 19 increasing attention to the highrisk elements of health care (such as patient care transitions), introducing redundancy and resilience into systems, 20 and implementation of appropriate information technology (such as prescription order entry systems).…”
Section: Discussionmentioning
confidence: 99%
“…Optimally, an anonymous web-based error reporting system should allow all staff to report errors without fear of consequence; nevertheless, this does not seem to be the case. Khare et al [9] found three factors preventing error reporting: fear, futility and hassle. It may be possible to create an environment in which error reporting is non-punitive, and the specter of litigation persists.…”
Section: Discussionmentioning
confidence: 99%
“…Exactly how many is unknown. Some believe that reported errors represent only a fraction of those that actually occur (Khare, Uren, & Wears, 2005).…”
Section: Overview Of Errors In the Emergency Departmentmentioning
confidence: 99%
“…Khare et al (2005) classified the barriers to error reporting into three factors: the fear factor, the futility factor, and the hassle factor. A staff member may feel fearful that he or she will be identified as the person who reported the error.…”
Section: Recovering and Reporting Medical Errors 99mentioning
confidence: 99%
See 1 more Smart Citation